Effect of Environmental Performance on Firm Value in Indonesian Stock Exchange: Intervening Role of Profitability - Muqorobin, Masculine Muhammad; Simamora, Alex Johanes (Journal of Trends Economics and Accounting Research, 2025)
This study aims to examine the effect of environmental performance on firm value, with profitability serving as a mediating variable. The research sample consists of 171 manufacturing companies listed on the Indonesia Stock Exchange and participating in the PROPER program during the period 2017–2019. Environmental performance is measured using the PROPER environmental performance rating. Firm value is measured using Tobin’s Q, while profitability is measured by return on equity (ROE). The analysis method employed includes regression analysis to test direct effects and the Sobel test to assess indirect effects. Based on the results of data analysis, this study demonstrates that (1) environmental performance has a positive effect on profitability, (2) profitability positively affects firm value, and (3) environmental performance also has a direct positive impact on firm value. Furthermore, the study confirms the mediating role of profitability, indicating that environmental performance indirectly enhances firm value through improved profitability. This research contributes to fulfil the inconsistent findings reported in prior Indonesian studies.